Assessing Awareness and Knowledge of Oral Cancer among Adult Dental Patients in Lahore, Pakistan (Medical Forum Monthly, 2024)
Objective: To determine the level of awareness and knowledge of oral cancer and its association with socio-demographic variablesStudy Design: Observational studyPlace and duration of study: The study was conducted at the Department of Prosthodontics, Lahore Medical and Dental College, Lahore from December 2014 to December 2015.Material and Methods: 952 participants of age 18 years and above participated. Sociodemographic information was obtained and a structured questionnaire comprising of 8 closed-ended questions assessed the general awareness and knowledge regarding oral cancer. SPSS version 22 was used for statistical analysis.Results: Majority had poor awareness (63.8%) and poor knowledge (82.88%) of oral cancer. A significant association was observed with age, gender, place of residence and education level.Conclusion: The overall awareness and knowledge of the population is lacking. It is recommended that more effort and time should be invested in public educational programs